1998
DOI: 10.1001/jama.280.13.1168
|View full text |Cite
|
Sign up to set email alerts
|

Age-Race Subgroup Compared With Renin Profile as Predictors of Blood Pressure Response to Antihypertensive Therapy

Abstract: Context.-Renin profiling and age-race subgroup may help select single-drug therapy for stage 1 and stage 2 hypertension. Objective.-To compare the plasma renin profiling and age-race subgroup methods as predictors of response to single-drug therapy in men with stage 1 and 2 hypertension as defined by the Joint National Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure. Design.-The Veterans Affairs Cooperative Study on Single-Drug Therapy of Hypertension, a randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(131 citation statements)
references
References 18 publications
6
123
1
1
Order By: Relevance
“…treating nephrolithiasis among younger, nonwhite populations (25,26). New trials conducted among populations that reflect the contemporary incidence of nephrolithiasis are needed.…”
Section: Discussionmentioning
confidence: 99%
“…treating nephrolithiasis among younger, nonwhite populations (25,26). New trials conducted among populations that reflect the contemporary incidence of nephrolithiasis are needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, more direct investigations of pre-treatment renin status in hypertensive blacks in relation to blood pressure response have demonstrated that the pretreatment PRA was not a particularly effective index of subsequent blood pressure response to pharmacological treatment. 24,[86][87][88][89] Nevertheless, other studies have demonstrated that the blood pressure reduction to short term sodium restriction was greater in blacks compared with whites; moreover, in the blacks, the greater reduction in blood pressure was significantly related, at least in part, to the decreased responsiveness of the renin-angiotensin system. 12 …”
Section: Functional Significance Of Lower Pra In Blacksmentioning
confidence: 99%
“…This supposed lack of effect has been attributed to the misperception that all of these patients have low-renin, salt-sensitive, volume-dependent hypertension. 5,6 In fact, blacks represent a heterogeneous population with respect to renin levels, 7 which may not accurately predict response to treatment. 8,9 Any difference in effect from other classes of antihypertensive agents is eliminated when angiotensin-converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs) are used in higher doses or in combination with a diuretic.…”
mentioning
confidence: 99%